Manajemen Operasional Pada Perusahaan Asuransi : Strategi Efisiensi Dan Kualitas Pelayanan - Farhan A; Ridho Afito (Ali Institute of Research and Publication, 2026)
This study aims to examine the operational management practices in insurance companies, focusing on business processes, operational efficiency, and service quality. The insurance industry has unique characteristics that require the integration of information technology, risk management, and responsive customer service. Through literature review and qualitative analysis of best practices, this paper identifies the key challenges and strategic solutions in operational management within the sector. The findings suggest that digitalization, process standardization, and performance measurement are essential elements in enhancing operational effectiveness and customer satisfaction. Keyword: Operational Management, Insurance Industry, Service Quality, Digital Transformation, Process Efficiency, Customer Experience